2021
DOI: 10.1016/j.aninu.2020.11.001
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of dietary addition of 2 essential oils from Achillea moschata, or their components (bornyl acetate, camphor, and eucalyptol) on in vitro ruminal fermentation and microbial community composition

Abstract: This study investigated the effects of 2 Achillea moschata essential oils extracted from plants collected in 2 different valleys of the Italian Alps and 3 pure compounds of oils — bornyl acetate (BOR), camphor (CAM), and eucalyptol (EUCA) — on in vitro ruminal fermentation and microbiota. An in vitro batch fermentation experiment (Exp. 1) tested the addition of all of the substances (2 essential oils and 3 compounds) in fermentation bottles (120 mL) at 48 h of incubation, whereas a subse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 47 publications
3
7
0
Order By: Relevance
“…Furthermore, [32] also reported that rumen bacteria would degrade the monoterpenes compounds during six hours of incubation. In this research, dosage of galangal EO is equal to 24% of cineole and similar results with [31] that cineole and A. moschata EO have different results on the rumen fermentation.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Furthermore, [32] also reported that rumen bacteria would degrade the monoterpenes compounds during six hours of incubation. In this research, dosage of galangal EO is equal to 24% of cineole and similar results with [31] that cineole and A. moschata EO have different results on the rumen fermentation.…”
Section: Discussionsupporting
confidence: 83%
“…Cineole, the main component of galangal EO, also has almost the same activity as phenol in the presence of an ether group that is reactive in binding lipase and reduce the bacterial activity. According to [31] the effects of Achillea moschata essential oil and three main components were consisting of d bornyl acetate (BOR), camphor (CAM), and eucalyptol (EUCA) have different effects on rumen microbes. Furthermore, [32] also reported that rumen bacteria would degrade the monoterpenes compounds during six hours of incubation.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, with its hydrophobic nature, cineole more easily crosses the plasma membrane of the protozoa and causes mitochondrial swelling. This study is almost the same as Colombini et al (2021) that adding Achillea moschata essential oil with cineole as the main compounds caused a decrease in the genus Euryarchaeota by 35.26%.…”
Section: Resultssupporting
confidence: 78%
“…For VFA determination, 1 ml of 25% meta-phosphoric acid was added to 5 ml of supernatant as described by Colombini et al ( 27 ). After 30 min, the mixture was centrifuged again at 3,500 × g for 10 min.…”
Section: Methodsmentioning
confidence: 99%